2001
DOI: 10.1084/jem.194.11.1609
|View full text |Cite
|
Sign up to set email alerts
|

Complement 1 Inhibitor Is a Regulator of the Alternative Complement Pathway

Abstract: We studied complement 1 inhibitor (C1-INH) as an inhibitor of the alternative complement pathway. C1-INH prevented lysis, induced by the alternative complement pathway, of paroxysmal nocturnal hemoglobinuria (PNH) erythrocytes in human serum. It inhibited the binding of both factors B and C3 to PNH and rabbit erythrocytes and blocked the ability of factor B to restore alternative-pathway function in factor B–depleted serum. C1-INH did not bind to factors B or D but did bind to immobilized C3b and cobra venom f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 21 publications
3
82
0
1
Order By: Relevance
“…C1 inhibitor also has been shown to inhibit alternative pathway activation via an incompletely defined mechanism which, however, does not require protease inhibition (Jiang et al, 2001). The data suggested that the findings might be of biologic relevance because removal of C1 inhibitor from plasma resulted in enhanced alternative pathway activation.…”
Section: Suppression Of Alternative Complement Pathway Activationmentioning
confidence: 69%
See 1 more Smart Citation
“…C1 inhibitor also has been shown to inhibit alternative pathway activation via an incompletely defined mechanism which, however, does not require protease inhibition (Jiang et al, 2001). The data suggested that the findings might be of biologic relevance because removal of C1 inhibitor from plasma resulted in enhanced alternative pathway activation.…”
Section: Suppression Of Alternative Complement Pathway Activationmentioning
confidence: 69%
“…Initial data suggest that, in some instances, these reactions may be significant contributors to the anti-inflammatory activity of this important protease inhibitor. These include at least four different binding reactions (Table 2): (1) An interaction with a variety of extracellular matrix components (Patston and Schapira, 1997); (2) inhibition of alternative complement pathway activation via binding of C1 inhibitor to C3b which prevents its interaction with factor B, in a manner analogous to that of factor H (Jiang et al, 2001); (3) an interaction with both E and P selectins on endothelial cells that is mediated by one or more Lewis x tetrasaccharides expressed on C1 inhibitor, and which results in suppression of leukocyte rolling and transmigration Cai et al, 2005); (4) binding to endotoxin from several different gram negative bacteria that results in suppression of endotoxin shock by interference with the interaction of endotoxin with its receptor complex on macrophages (Liu et al, 2003;Liu et al, 2004;Liu et al, 2005a;Liu et al, 2005b); (5) direct binding to gram negative bacteria that results in suppression of the development of sepsis (unpublished data). This review will briefly summarize the limited information available on the first two reactions and will describe in more detail the data relating to the interactions with selectins and with endotoxin lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…It is the sole natural inhibitor of C1r and C1s, is an inhibitor of the lectin pathway via inactivation of mannan-binding lectin-associated serine proteinase-1 and 2, and inhibits the alternative pathway of activation by binding to C3b (1). It is also the major regulator of coagulation factors XI and XII, and of plasma kallikrein (for review, see Ref.…”
Section: Inhibitor (C1inh)mentioning
confidence: 99%
“…Complement component C1 esterase inhibitor (C1-INH) is an important regulator of many plasma mediator pathways, including the complement system. Jiang et al (16) in their study showed that C1-INH inhibits alternative pathway activation by inhibiting the activities of factor B and the cleavage of C3 indirectly through C3b and that the removal of C1-INH restored remarkably the activities of the pathway. Our study showed higher serum C1-INH in the SCD patients compared to the controls, which could also suggest a defective alternative complement pathway in Nigerian SCD patients.…”
Section: Discussionmentioning
confidence: 99%